2016
DOI: 10.7448/ias.19.1.20926
|View full text |Cite
|
Sign up to set email alerts
|

Retention and mortality outcomes from a community‐supported public–private HIV treatment programme in Myanmar

Abstract: IntroductionThere is a growing interest in the potential contribution the private sector can make towards increasing access to antiretroviral therapy (ART) in low- and middle-income settings. This article describes a public–private partnership that was developed to expand HIV care capacity in Yangon, Myanmar. The partnership was between private sector general practitioners (GPs) and a community-based non-governmental organization (International HIV/AIDS Alliance).MethodsRetrospective analysis of 2119 patient r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 42 publications
(65 reference statements)
2
6
0
Order By: Relevance
“…There is limited literature investigating the association of other clinical characteristics with missed visits, especially in resource-limited settings. However, our results are comparable to reported studies which showed that younger patients, males, and those with hepatitis C co-infection were more likely to have discontinuous engagement in care(Asiimwe, Kanyesigye, Bwana, Okello, & Muyindike, 2016; Mburu et al, 2016; Megerso et al, 2016; Rachlis et al, 2016; F. Zhang et al, 2014).…”
Section: Discussionsupporting
confidence: 88%
“…There is limited literature investigating the association of other clinical characteristics with missed visits, especially in resource-limited settings. However, our results are comparable to reported studies which showed that younger patients, males, and those with hepatitis C co-infection were more likely to have discontinuous engagement in care(Asiimwe, Kanyesigye, Bwana, Okello, & Muyindike, 2016; Mburu et al, 2016; Megerso et al, 2016; Rachlis et al, 2016; F. Zhang et al, 2014).…”
Section: Discussionsupporting
confidence: 88%
“…A study in rural Uganda and Kenya found that delay in ART initiation of more than 30 days after HIV diagnosis was associated with elevated rates of treatment dropout at 12 months [22]. In Myanmar, 94% of ART-eligible study participants were on ART by 90 days, and only 3% had dropped out of treatment in a median of 13 months of follow-up [23]. A very large, retrospective analysis of newly diagnosed PLWH in high-income countries has found that immediate initiation of ART increases viral suppression earlier in follow-up [24].…”
Section: Discussionmentioning
confidence: 99%
“…The Ugandan study’s cumulative death rate of 22.7% similarly had 63% of deaths occurring within one year of initiating ART. Another Myanmar study of a five-year program in Yangon, the country’s most populous city and former capital, found that 39.8% of deaths occurred six months after ART initiation [ 16 ], and multivariate analysis suggested that only ART exposure status and baseline CD4 count were independently predictive of mortality.…”
Section: Discussionmentioning
confidence: 99%